The fight against cancer: Is it worthwhile? - Barreto, Savio George; Barreto, Merlyn; Chaubal, Rohan; Dutt, Amit (Indian Journal of Medical and Paediatric Oncology, 2015)
This article alludes to the findings of Tomasetti and Vogelstein and argues that for clinicians and scientists no matter how difficult understanding the pathogenesis of cancer may be, they remain the only hope for patients suffering from the disease. Data citing wide differences in cancer incidence in different parts of the world is presented to drive home the point that ′Bad luck′ is not a good enough explanation for cancer pathogenesis. There remains a lot to be uncovered in cancer and clinicians and scientists should strive to this end.
Keywords: genetic risk for cancer; global cancer epidemiology; cancer pathogenesis